Universal all in fiber coherent light source at the wavelength 1550 nm and output power 5 W - Kaczmarek, Paweł; Soboń, Grzegorz; Wąż, Adam; Dudzik, Grzegorz; Antończak, Arkadiusz J.; Abramski, Krzysztof M. (Photonics Letters of Poland, 2014)
A continuous-wave (CW) and Q-switched operation of a Ho:YLF laser resonantly, single-pass pumped by a Tm: fiber laser operating at a wavelength of 1940nm is presented. At room temperature, for an output coupler of 40% transmission, a maximum CW output power of 11.5W for 32.5W of incident pump power was achieved, corresponding to a slope efficiency of 40%. Applying Q-switching operation, and under CW pumping regime, the pulse repetition frequency (PRF) was changed from 1 to 10kHz. The maximum average output power of 11.23W at the PRF of 10kHz was obtained. Lowering the PRF to 1kHz allows achieving pulse energy of 4.97mJ in a 19ns pulse corresponding to the maximum peak power of 260kW. The Ho:YLF laser operated at the wavelength of 2050.5nm with a FWHM line width of 1.09nm. The output parameters of the laser radiation are sufficient enough to be used for range finding or for pumping mid-infrared optical parametric oscillators. In this paper we present fiber based coherent light source operating at 1550 nm wavelength and 5 W of the output power. It utilizes Master Oscillator Power Amplifier scheme of operation. This allowed to get a universal design which can work in couple different operation regimes: CW, pulsed and wideband ASE generation. All in fiber construction makes it to be compact and environmental conditions resistant. Full Text: PDF References K. Scholle, S. Lamrini, P. Koopmann, P. Fuhrberg, chapter 21 in Frontiers in Guided Wave Optics and Optoelectronics, INTECH, ISBN 978-953-7619-82-4, 2010. Nilsson J., Jeong Y., et al, "High-power fiber lasers: progress and opportunities", LPHYS'05: 14th International Laser Physics Workshop, Kyoto, Japan, 4-8 Jul 2005. Yong W., Martinez-Rios A., Hong P., "Experimental study of stimulated Brillouin and Raman scatterings in a Q-switched cladding-pumped fiber laser", Optical Fiber Technology, Vol. 10, Issue 2, April 2004, pp. 201-214. CrossRef Wysocki P., Wood T., Grant A., Holcomb D., Chang K., Santo M., Braun L., and Johnson G., "High Reliability 49 dB Gain, 13W PM Fiber Amplifier at 1550 nm with 30 dB PER and Record Efficiency", Optical Fiber Conference (OFC), paper PDP17, 2006. Lee J.H., Kim C.H., Han Y.-G. and Lee S.B., "Broadband, high power, erbium fibre ASE based CW supercontinuum source for spectrum-sliced WDM PON applications", Electronics Lett. Vol. 42 No. 9 pp. 67-68. CrossRef Wright M.W., Valley G.C., "Yb-Doped Fiber Amplifier for Deep-Space Optical Communications", Journal Of Lightwave Tech., Vol.23, No.3, pp.1369-74, March 2005. CrossRef Anthon D., Fisher J., Keur M., Sweeney K. and Ott D., "High power optical amplifiers for CATV applications", Optical Fiber Communication Conference and Exhibit, OFC 2001, Vol.2, pp. TuI1-1-TuI1-3, 2001. Kaczmarek, P.R., Soboń, G., Sotor, J.Z., Antończak, A.J., Abramski, K.M., "Fiber-MOPA sources of coherent radiation", Bulletin of the Polish Academy of Sciences: Technical Sciences 58 (4), pp. 485-489, 2010 DirectLink Sobon, G., Kaczmarek, P., Antonczak, A., Sotor, J., Waz, A., Abramski, K.M., "Pulsed dual-stage fiber MOPA source operating at 1550 nm with arbitrarily shaped output pulses", Applied Physics B: Lasers and Optics 105 (4), pp. 721-727, 2011 CrossRef Sobon, G., Kaczmarek, P., Antonczak, A., Sotor, J., Abramski, K.M., "Controlling the 1 μm spontaneous emission in Er/Yb co-doped fiber amplifiers", Optics Express 19 (20), pp. 19104-19113, 2011 CrossRef